FAKTOR- FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI SALAK DI DESA PARSALAKAN ANGKOLA BARAT TAPANULI SELATAN - Nasution, Nora Efrita; Sagala, Edison (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Medan, 2016)
Factors of production farming has a different function to level of production and farmers income. The better use factors of production, the amount of production is produced also more and more so that income received by farmers is higher. This study aims to determine whether education, experience, land, and capital affect farmers income. The population in this study were all barking farmers in the village of Persalakan Angkola Barat South Tapanuli. The sampling technique in studies using methods Solvin with a total sample of 50 farmers bark. Data collection techniques used observation and questionnaires. The data analysis technique used is multiple linear analysis to prioritize testing and classical assumption of normality as a condition of continued analysis. From the results of analysis can be concluded the factor of land area education and partially no effect on farmers income while the experience factor, capital, Extension and Number of dependents has a positive and significant impact on farmers income in the village of Persalakan Angkola Barat South Tapanuli. Keywords: Education, Experience, Land, Capital, Counseling, Number of dependents, income